Empowering refugees and asylum seekers in the Italian agriculture sector by linking social cooperative entrepreneurship and social work practices. (12th August 2020) - Lintner, Claudia; Elsen, Susanne
Abstract : The present study investigated the potential of social cooperative activities and social work practices in the Italian agriculture sector in promoting sustainable integration forms for refugees and asylum seekers. The study adopted a qualitative approach using case study as the main research method. As the results show, the complexity and diversity of needs of refugees and asylum seekers make collaboration between formal and informal actors increasingly necessary for generating a common knowledge and support networks. The article argues that integrated approaches to refugees' socio‐economic integration are needed to free them from the need for assistance and thereby help them regain their autonomy. The case study presented gives insight into the potential of small‐step experiences towards sustainable development and, linked to this, the integration of refugees and asylum seekers based on self‐organisation and cooperation, considering the well‐being of all citizens in the broader context.